Treatment of an adult patient with severe dental crowding by applying asymmetric extraction, fixed appliance, and micro-implant anchorage: a case report - Huixin Xue; Siyi Xu; Yezi Qi; Leilei Xue; Xinxin Ni; Liqi Xu; Qingshan Li; Jun Lin (BMC Oral Health)
Abstract Background Severe dental crowding and protrusion often necessitate symmetric extraction for correction. However, asymmetric extraction may serve as a viable, albeit challenging, treatment option when the prognosis of individual tooth is poor. In this report, we present a case where asymmetric extraction was employed to address severe dental crowding and deviated midlines, resulting in satisfactory outcomes following retention. Case presentation We report a case of a 31-year-old woman with severe dental crowding and deviated dental midlines. A fixed appliance, micro-implant anchorage, and asymmetric extraction, including a mandibular canine with severe buccal malposition, were applied to the patient. The treatment outcomes demonstrated successful achievement of the treatment objectives, with well-aligned teeth exhibiting solid interdigitation and the dental midlines aligned with the facial midline. At the 21-month follow-up, midline stability, favorable occlusal interdigitation, and improved smile line were observed. Conclusions Asymmetric extraction may be considered a viable approach for patients with individual tooth of poor prognosis. Treatment stability can be achieved through well-interdigitated occlusion and the use of various retention methods.